2022
DOI: 10.1007/s00198-022-06470-3
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of denosumab on muscle performance in patients with low BMD: a retrospective, propensity score-matched study

Abstract: This study examined the effects of denosumab compared to bisphosphonates and vitamin D alone on muscle performance in patients with low BMD. While grip force improved in both the denosumab and bisphosphonate group, a superior increase in chair rising test force was observed in the denosumab group. Introduction The aim of this study was to investigate the effect of the anti-resorptive agent denosumab (Dmab) on upper and lower limb muscle performance compared to bisphosphonate (BP) treatment and vitamin D supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Rupp et al 22 ) showed that denosumab also has better outcomes in FN BMD compared to bisphosphonate. The mean annual percentage changes in FN BMD were higher in the denosumab and bisphosphonate groups and were significantly higher compared to the basic group—mean FN BMD in % change per year: basic (-0.78%±2.12%), bisphosphonate (0.68%±2.54%), and denosumab (1.83%±2.66%).…”
Section: Resultsmentioning
confidence: 99%
“…Rupp et al 22 ) showed that denosumab also has better outcomes in FN BMD compared to bisphosphonate. The mean annual percentage changes in FN BMD were higher in the denosumab and bisphosphonate groups and were significantly higher compared to the basic group—mean FN BMD in % change per year: basic (-0.78%±2.12%), bisphosphonate (0.68%±2.54%), and denosumab (1.83%±2.66%).…”
Section: Resultsmentioning
confidence: 99%
“…Current studies have shown conflicting results between anti-osteoporosis treatment and improvement of sarcopenia, with some drugs relying on a common pathway between the bone and muscle to improve sarcopenia alongside anti-osteoporosis treatment, such as denosumab and tibolone 64 , 65 . It is still unknown whether altering the ratio of cells in the skeleton without the common pathway can have an effect on muscle output, while studies on the effect of denosumab on muscle through the common pathway are very scarce, lacking control groups and considering the effect of protein intake and exercise interventions 66 .…”
Section: Current Treatments For Sarcopeniamentioning
confidence: 99%
“…For example, Fig. 3 illustrates a comparison of mean change in hand grip strength between denosumab users and bisphosphonate users from Miedany et al 2) and a comparison between denosumab users and no therapy from the other two studies (Bonnet et al 3) and Rupp et al 4) ). Furthermore, the Bonnet hand grip strength data in the meta-analysis are incorrect because corrected hand grip strength data published in a 2020 corrigendum 5) to the Bonnet et al 3) paper were not considered.…”
Section: Dear Editormentioning
confidence: 99%